1998
DOI: 10.1038/sj.dmfr.4600319
|View full text |Cite
|
Sign up to set email alerts
|

Volumetry of bone grafts by three-dimensional computed tomographic reconstruction: an animal study in the minipig.

Abstract: The volume of a bone graft can be determined by 3D-CT. However, further refinements of the technique are needed to improve the accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…; Jensen et al. ). Volumetric analysis based on either CT scanning or magnetic resonance imaging (MRI) is the best tool for volume determination.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Jensen et al. ). Volumetric analysis based on either CT scanning or magnetic resonance imaging (MRI) is the best tool for volume determination.…”
Section: Discussionmentioning
confidence: 97%
“…In this context, three‐dimensional computerized tomography (3D CT scan) assesses the correlation between the real volume measurements of bone grafts and the volumes measured by the 3D CT scan, to determine the accuracy of this type of examination (Jensen et al. ). Uchida et al.…”
Section: Year Author Exam Materials Sample T1 T2 Tf Dc‐t2 Dc‐tfmentioning
confidence: 99%
“…We calculated the relative percentage of bone rather than the absolute value as the outcome variable. This method was chosen to avoid systematic measurement errors related to variations in pixel size, variability in specimen size, accidental angulation of the specimen in the gantry 19 , possible overestimation of absolute volumes by averaging inherent to CT 16 , and to account for variability in distraction gap size. A special purpose scanner was used to minimize error and ensure reproducibility 15,26 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study 3D CT scans were used to assess the defect volume after the grafting. This method seems to be accurate as reported by Jensen et al (1998) who showed a strong correla-tion between the 3D reconstructions of the predefined graft volume based on axial CT scans and calculated graft volume according to the Archimedes principle. 15 In the literature, there are many reports involving long-term success rates of secondary bone grafting based on computed tomography.…”
Section: Discussionmentioning
confidence: 93%
“…This method seems to be accurate as reported by Jensen et al (1998) who showed a strong correla-tion between the 3D reconstructions of the predefined graft volume based on axial CT scans and calculated graft volume according to the Archimedes principle. 15 In the literature, there are many reports involving long-term success rates of secondary bone grafting based on computed tomography. Rosenstein et al (1997) investigated the agreement between 3D and 2D assessment and found out that although 2D method can be used in evaluating bone-graft success for a group of UCLP patient, 3D computed tomography is still a superior, and probably the only assessment method for determining the volumetric bone support for cleft-adjacent teeth in certain clinical situations in which great accuracy were called.…”
Section: Discussionmentioning
confidence: 93%